1976
DOI: 10.2466/pms.1976.43.2.587
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Ratio Discrimination: Comparison of Spatial and Nonspatial Choice Procedures

Abstract: 3 pigeons were trained on a conditional discrimination in which fixed-ratio 10 and fixed-ratio 20 were randomly scheduled on the center of 3 response keys. Reinforcement was contingent upon the choice of a green side key on fixed-ratio 10 trials and upon a red side key on fixed-ratio 20 trials. Performance was compared on alternating spatial and nonspatial sessions. During spatial sessions, red was always presented on the left-side key and green was always presented on the right. During nonspatial sessions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Although birds failed to acquire a pure autoshaping response in ARENA, they readily acquired a simple instrumental response (Experiment 1), a simple discrimination (Experiment 2), and a more complex conditional discrimination (Experiment 3). The patterns of behavior shown in ARENA were comparable to those found in similar experiments using conventional open-field procedures and automated systems like operant chambers equipped with either keylights or a touchscreen (e.g., Brodigan & Peterson, 1976; Cole & Honig, 1994; Emmerton, 2001; Kendall, 1983; Nevin, 1967; Perkins, Lydersen, & Chairez, 1976; Reynold & Limpo, 1969). …”
Section: Methodssupporting
confidence: 70%
“…Although birds failed to acquire a pure autoshaping response in ARENA, they readily acquired a simple instrumental response (Experiment 1), a simple discrimination (Experiment 2), and a more complex conditional discrimination (Experiment 3). The patterns of behavior shown in ARENA were comparable to those found in similar experiments using conventional open-field procedures and automated systems like operant chambers equipped with either keylights or a touchscreen (e.g., Brodigan & Peterson, 1976; Cole & Honig, 1994; Emmerton, 2001; Kendall, 1983; Nevin, 1967; Perkins, Lydersen, & Chairez, 1976; Reynold & Limpo, 1969). …”
Section: Methodssupporting
confidence: 70%
“…Renouf and Gaborko (1989) suggested that the apparent ease with which the seals learned the spatial tasks compared to the visual tasks might suggest something about the relative importance of such cues to these animals. Many researchers have suggested that animals appear to rely on spatial cues more readily than other types of cues (e.g., Chiszar & Spear, 1969; Gossette & Brown, 1967; Pagani, Brown, & Stanton, 2005; Perkins, Lydersen, & Chairez, 1976; Thomas, McKelvie, & Mah, 1985). This is especially true of insects, such as many ant and bee species, which rely on spatial contextual cues for navigation during daily foraging trips (see Collett, Fauria, & Dale, 2003, for a review).…”
mentioning
confidence: 99%